Prevajanje pri pouku tujega jezika: poučevanje ruskega jezika s pomočjo angleških literarnih prevodov - Kaloh Vid, Natalia (Slavia Centralis, 2020)
Translation in the Foreign Language Class: Teaching Russian through English Literary TranslationsThe following article focuses on the use of re-translations in the course Russian as a foreign language and suggests translation activities that help the students to improve their knowledge of the Russian language by reading, analyzing and discussing re-translations. This method was used in the second part of the 60-hour elective course Russian Language I, once the students were familiar with the Cyrillic alphabet and were able to read shorter texts. English re-translations of Russian literary texts were used. The students focused primarily on recognizing and translating culturally specific elements. The aim of the activity was to stimulate students’ interest in a foreign cultural environment and to enable them to use the existing knowledge of the foreign language and their imagination instead of dictionaries and glossaries. In the second phase of the activity, students presented their solutions and ideas and shared their experience with the professor.
Keywords: Russian language; translation; teaching; re-translating